(untitled) (International Journal of Engineering and Computer Science, 2018)
Image segmentation is the process of partitioning an image into meaningful components or structures based on color, shape, intensity etc. Image segmentation plays an important role in the field of image analysis, it can also be used for object recognition, visualization and many other image processing tasks. Image segmentation is used to classify or to cluster the image into several parts according to the features extracted from the image. The main goal of the segmentation is to make the image easier to analyze. The output of the segmentation is a set of segments that will cover the entire image. This paper presents the various image segmentation techniques, their merits and demerits.